2017
DOI: 10.3847/1538-4365/aa71a3
|View full text |Cite
|
Sign up to set email alerts
|

VLBI Ecliptic Plane Survey: VEPS-1

Abstract: We present here the results of the first part of the VLBI Ecliptic Plane Survey (VEPS) program. The goal of the program is to find all compact sources within  7 . 5 of the ecliptic plane that are suitable as calibrators for anticipated phase referencing observations of spacecraft, and determine their positions with accuracy at the 1.5nrad level. We run the program in two modes: search and refine. In the search mode, a complete sample of all sources brighter than 50 mJy at 5 GHz listed in the Parkes-MIT-NRAO … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…For our analysis we use the same 8 GHz VLBI data as in Plavin et al (2020) that are compiled in the Astrogeo 1 database. These observations include geodetic VLBI programs (Petrov et al 2009;Piner et al 2012), the Very Long Baseline 1 http://astrogeo.org/vlbi images/ Array (VLBA) calibrator surveys (VCS; Beasley et al 2002;Fomalont et al 2003;Petrov et al 2005Petrov et al , 2006Kovalev et al 2007;Petrov et al 2008;Petrov 2017;Gordon et al 2016), and other 8 GHz global VLBI, VLBA, EVN (the European VLBI Network), LBA (the Australian Long Baseline Array) observations (Petrov et al 2011a;Petrov 2011;Petrov et al 2011b;Petrov 2012Petrov , 2013Schinzel et al 2015;Shu et al 2017;Petrov et al 2019;Petrov 2020;Popkov et al 2020). The AGN positions are determined from these observations and presented within the VLBI-based Radio Fundamental Catalogue 2 (RFC).…”
Section: Vlbi Observations Of Agnsmentioning
confidence: 99%
“…For our analysis we use the same 8 GHz VLBI data as in Plavin et al (2020) that are compiled in the Astrogeo 1 database. These observations include geodetic VLBI programs (Petrov et al 2009;Piner et al 2012), the Very Long Baseline 1 http://astrogeo.org/vlbi images/ Array (VLBA) calibrator surveys (VCS; Beasley et al 2002;Fomalont et al 2003;Petrov et al 2005Petrov et al , 2006Kovalev et al 2007;Petrov et al 2008;Petrov 2017;Gordon et al 2016), and other 8 GHz global VLBI, VLBA, EVN (the European VLBI Network), LBA (the Australian Long Baseline Array) observations (Petrov et al 2011a;Petrov 2011;Petrov et al 2011b;Petrov 2012Petrov , 2013Schinzel et al 2015;Shu et al 2017;Petrov et al 2019;Petrov 2020;Popkov et al 2020). The AGN positions are determined from these observations and presented within the VLBI-based Radio Fundamental Catalogue 2 (RFC).…”
Section: Vlbi Observations Of Agnsmentioning
confidence: 99%
“…We should stress that all these listed problems can be solved with existing facilities under dedicated program. At the same time, attempts to add some sources to regular geodetic VLBI observations (Le Bail et al 2016;Shu et al 2017) turned out only partly successful. Improvement of source position coordinates with a pace of 30-100 sources per year is not sufficient to make a noticeable difference.…”
Section: Future Observationsmentioning
confidence: 99%
“…It is not uniform for both all the sources and sources having photometric and redshift data, with a deficit in the southern hemisphere. Additionally, densification of sources near the ecliptic coming from Shu et al (2017) and dispersion of sources near the Galactic plane are observed. A jump in the source distribution at δ ≈ 40 • corresponds to the southern boundary of the declination zone available for the Very Long Baseline Array (VLBA) that provided observations of most astrometric radio sources.…”
Section: General Catalog Descriptionmentioning
confidence: 87%